Claire Havenhill: capstone - Havenhill, Claire, artist (Colorado State University. Libraries, 2025)
The artist's statement: Creating art has always been my personal outlet for processing complex emotions, using it to communicate my inner monologue, especially when unable to synthesize thoughts into words. Conceptually, my work tends to initially catalyze from internal struggles, often addressing issues of self-perception, sense of place, and personal evolution in the context of the world around me. I frequently take an iconographic approach to storytelling, using unique arrangements of universal motifs, commonly from the natural world, to communicate my message to a wider audience. My work often mirrors widespread idioms, expressions, and folklore, which I use as means of connecting my internal conscience to the universal human experience. As an artist, printmaking is where my artistic passion lies. I have a deep appreciation for the endless possibilities of print media and am continuously entranced by its process-based nature. Though printmaking is known as a method of producing identical multiples, I often create variable editions to give each print an individual, unique touch. I choose to work primarily with traditional stone lithography, drawn to its technically complex and procedural nature that is equally challenging, frustrating, and rewarding. Visually, I gravitate to printmaking because of its unique textural capabilities, in which I often overlap with iconographic and illustrative scenes. Working with this craft requires me to practice trust, resilience, and adaptability in my making process, forcing me to accept my failures and persist, nonetheless. These core aspects of printmaking appropriately mirror my purpose in making art, which exists as my main means of processing every corner of my life.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking